Comprender y mejorar la conducta trabajando en grupo : una metodología centrada en el alumno - Hunter, Cath (Herramientas Narcea ;, 2016)
This book provides insight in how to respond in a way that provides positive messages, increases their emotional vocabulary, and encourages them to change their behavior. It offers a child-centered way of managing children's behavior through introducing the concept of reflective language and other tools, equipping staff with new skills that are transferable across the school in any role.